Diagnosing fetal alcohol syndrome: new insights from newer genetic technologies. Issue 9 (14th July 2012) - Douzgou, Sofia; Breen, Catherine; Crow, Yanick J; Chandler, Kate; Metcalfe, Kay; Jones, Elizabeth; Kerr, Bronwyn; Clayton-Smith, Jill
Abstract : Objective: A genetic opinion is frequently requested in the assessment of a child with suspected fetal alcohol spectrum disorders (FASD). We studied the outcome of genetic assessment of 80 children referred to a regional genetics centre between 2004 and 2010 to identify the value of the genetic assessment in cases of suspected FASD. Design: Retrospective case series. Patients: 80 patients, aged between 1 month and 26 years. Methods: Data from the medical records was abstracted, entered onto a standard study pro forma, recorded in an Excel spreadsheet and analysed using simple frequency analysis. Results: In 20% of cases fetal alcohol syndrome was confirmed at the genetic consultation. The most common facial features were thin upper lip (86.6%) and short palpebral fissures (82%). A lip–philtrum score of 4 or 5 was identified in two-thirds of cases. The most common alternative diagnosis was a chromosome disorder, representing 8.75% of the FASD referrals. Setting: A regional genetics service in the North West of England. Conclusions: Genetic assessment was of particular value in excluding other diagnoses and providing information to carers. Two-thirds of the children referred were subject to a care order increasing the difficulty to obtain a family and alcohol exposure history. Classification of FASD was difficult in children under a year old when data on growth and development were limited. Structural malformations were not common in the group overall and some previously reported diagnostic signs were not found to be reliable markers of FASD. Chromosome disorders showed phenotypic overlap with FASD and are an important differential diagnosis.